Analisis Konten Website CV. MyPangandaran dalam Penerapan Strategi Komunikasi Pemasaran - Dally Nur Arif; Enjang Yusup Ali; Tirza Rema Purnamasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Communication plays a crucial role in marketing, serving as a tool to inform, remind, and bridge companies with the public in introducing products. CV. MyPangandaran, with a wider target of tourists outside Pangandaran Regency, faces challenges in reaching audiences through www.mypangandaran.com website. To maximize the reach of a website, an effective marketing communication strategy is needed. This study uses a qualitative method with a content analysis approach, focusing on documentation studies as primary data. The goal is to review the marketing communication strategy implemented by CV. MyPangandaran in an effort to expand the reach and increase the effectiveness of promotion. The results of the study show that the marketing communication strategies implemented include advertising, content marketing, direct marketing, and social media marketing. In the application of marketing mix theory, the communication aspect is the most dominant. Meanwhile, the most prominent AIDA (Attention, Interest, Desire, Action) model is the interest aspect. CV. MyPangandaran adjusts the advertising strategy to the characteristics of the products sold. Direct marketing is directed at the target market aged 25-35 years. The company also utilizes social media as a supporting marketing communication tool, including Facebook, Instagram, Twitter/X, and TikTok.This integrated marketing communication strategy aims to expand reach, increase engagement, and maximize the effectiveness of CV product and service promotions. MyPangandaran to potential tourists outside Pangandaran Regency. By integrating various communication channels, the company seeks to build brand awareness and increase tourist interest in Pangandaran destinations.